(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The fragment of the ancient fortress wall of the city of Bukhara that has survived to this day is a unique monument of the cultural architecture of Bukhara. The walls and gates of the Bukhara Fortress are one of the historical sites demonstrating the tourism potential of Uzbekistan. They also serve for events, elections and other opportunities for tourists. A visit to the Bukhara Fortress provides an opportunity to get acquainted with experienced guides, historical exhibitions and cultural heritage. This article presents scientific approaches and proposals to the spatial planning solution of fortress walls and gates and their role in urban planning.